KUALITAS TUGAS AKHIR MAHASISWA - Mardiati Busono (Universitas Negeri Yogyakarta, 1999)
The average length of srudy of he students of the Dept. of Special Education of the academic year 197/lW used to be 6.12 years and none of the students gradwted with a predicue cum laude. Research on study obstacles has not yet